Smooth muscle cells from the anastomosed artery are the major precursors for neointima formation in both artery and vein grafts - Liang, Ming (Basic Res Cardiol, 2014)
Accumulation of smooth muscle cells (SMC) results in neointima formation in injured vessels. Two graft models consisting of vein and artery grafts were created by anastomosing common carotid arteries to donor vessels. To identify the origin of the neointima cells from anastomosed arteries, we use Wnt1-Cre/reporter mice to label and track SMCs in the common carotid artery. The contribution of SMCs in the neighboring arteries to neointima formation was studied. On evaluating the artery grafts after 1 month, >90 % of the labeled neointima cells were found to have originated from the anastomosing host arteries. Most of the neointima cells were also smooth muscle α-actin positive (SMA-α(+)) and expressed the smooth muscle myosin heavy chain (SMMHC), the SMC terminal differentiation marker. In vein grafts, about 60 % SMA-α-positive cells were from anastomosing arteries. Bone marrow cells did not contribute to neointima SMCs in vein grafts, but did co-stain with markers of inflammatory cells. Wnt1 expression was not detected in the neointima cells in the vein or artery grafts, or the injured femoral arteries. Neointima SMCs showed the synthetic phenotype and were positively labeled with BrdU in vitro and in vivo. Treatment with the IGF-1 receptor inhibitor suppressed SMC proliferation and neointima formation in vein grafts. Our results indicate that SMCs from the neighboring artery are predominantly present in the neointima formed in both vein and artery grafts and that Wnt1-Cre mice can be used to explore the role of SMCs originating from neighboring vessels in vascular remodeling.